2014
DOI: 10.1270/jsbbs.64.213
|View full text |Cite
|
Sign up to set email alerts
|

Level of <i>VERNALIZATION 1</i> expression is correlated with earliness in <i>extra early-flowering</i> mutant wheat lines

Abstract: Four extra early-flowering mutants, named extra early-flowering1 (exe1), exe2, exe3, and exe4, were identified in Triticum monococcum strain KU104-1 following heavy-ion beam mutagenesis. The four exe mutants fell into two groups, namely Type I (moderately extra early-flowering type; exe1 and exe3) and Type II (extremely extra early-flowering type; exe2 and exe4). Analysis of plant development in a growth chamber showed that the speed of leaf emergence was accelerated in exe mutants at the reproductive stage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 34 publications
5
24
0
Order By: Relevance
“…Since the transcript abundance of Vrn-1 and WFT are often correlated with heading time in wheat [7], we examined the expression of these genes in ‘Chogokuwase’ and its parental cultivars. Vrn-1 transcript levels were significantly higher in ‘Chogokuwase’ than in the parental cultivars at all 4L stages under V0-LD, V21-LD and V21-SD conditions (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the transcript abundance of Vrn-1 and WFT are often correlated with heading time in wheat [7], we examined the expression of these genes in ‘Chogokuwase’ and its parental cultivars. Vrn-1 transcript levels were significantly higher in ‘Chogokuwase’ than in the parental cultivars at all 4L stages under V0-LD, V21-LD and V21-SD conditions (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…All of the early heading F 2 plants in the MG population had the dominant VRN-D1 allele (Fig 6). Our preceding experiment demonstrated that Vrn-1 expression levels in leaves were associated with earliness [7]. Therefore, VRN-D1 might be a candidate gene that confers early heading in ‘Chogokuwase’, a hypothesis that remains to be tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can survive extreme temperatures through the vegetative (-35°C) to grain filling (40°C) phases and is grown under different climatic conditions from Australia to Canada (Reynolds et al, 2009;Kamran et al, 2013). Vernalization (VRN) and photoperiod (PPD) are the (very wellstudied) major gene systems that control flowering time in wheat (Yan et al, 2003;Li et al, 2011;Chen and Dubcovsky, 2012;;Zheng et al, 2013;Eagles et al, 2014;Guedira et al, 2014;Nishiura et al, 2014). Vernalization (VRN) and photoperiod (PPD) are the (very wellstudied) major gene systems that control flowering time in wheat (Yan et al, 2003;Li et al, 2011;Chen and Dubcovsky, 2012;;Zheng et al, 2013;Eagles et al, 2014;Guedira et al, 2014;Nishiura et al, 2014).…”
Section: Researchmentioning
confidence: 99%
“…VRN1 encodes an APETALA1 (AP1)/FRUIT-FULL-like MADS box transcription factor that is upregulated by vernalization (Danyluk et al, 2003;Murai et al, 2003;Trevaskis et al, 2003;Yan et al, 2003). The level of VRN1 expression is correlated with the level of expression of the wheat florigen gene Wheat FLOWERING LOCUS T (WFT, which is identical to VRN3) (Shimada et al, 2009;Nishiura et al, 2014). Expression of VRN1 gradually increases during the seedling growth stage without vernalization (Nishiura et al, 2014), suggesting that the expression of VRN1 is also controlled by internal signals such as aging.…”
mentioning
confidence: 99%